Effects of old age on fatigability and sensorimotor characteristics of a repetitive upper limb fatiguing task - Bailey, Christopher A. (PLoS One, 2020)
OBJECTIVES: 1) Determine the effects of old age on sensorimotor responses to a fatiguing work-like task. 2) Explore how old age influences the relationships between task fatigability, everyday perceptions of fatigability, and sensorimotor function. METHODS: Healthy young (N = 17, 9W) and older (N = 13, 10W) adults completed the Pittsburgh Fatigability Scale to assess everyday perceptions of physical (PF) and mental fatigability and performed a repetitive tapping task to fatigue. Before and after the task, grip strength was assessed using a hand-grip dynamometer and touch-pressure sensitivity was measured (shoulder, hand) using Semmes-Weinstein monofilaments. RESULTS: Older, but not young adults, had increased touch-pressure sensitivity at the shoulder after fatigue (interaction, p = 0.007). No changes in grip strength were observed (p>0.05). Task fatigability was not different between young and old adults (p>0.05). Having less task fatigability was associated with lower PF, higher grip strength, and higher touch-pressure sensitivity at the hand (ρ = 0.37–0.58, p<0.05), with the hand sensation association also observed in the old adult subgroup (ρ = 0.56, p = 0.046). CONCLUSIONS: With old age, there were fatigue-related alterations to sensory but not physical function. While task fatigability was associated with perceptual, physical, and sensory features, sensory features appear to have a more important role with old age.